URGENSI PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK PADA ANAK STUDI KASUS TK NEGERI PEMBINA LANRISANG - Ahmad Ahmad; Yusriah (IAI DDI POLEWALI MANDAR, 2023)
This study discusses the urgency of Islamic religious education in fostering morals in case study children at the Lanrisang State Kindergarten. The problems that arise in this study are 1) how is Islamic religious education in the public kindergarten fostering lanrisang 2) how is the moral development of children in the fostering public kindergarten lanrisang 3) what is the impact of Islamic religious education in fostering morals in children fostering public kindergarten lanrisang. Using field research (field research) which is qualitative descriptive. Data collection techniques were carried out by observation, interview and documentation methods. The subjects in this study were school principals, educators and parents of Lanrisang State Kindergarten students. The results of this study indicate that, Islamic education in the Lanrisang Guidance Public Kindergarten is every day students are given Islamic education in a systematic and continuous manner which includes education on faith, worship and morals. Students are given basic material on faith (pillars of Islam) trained to have good character (akhlakul karimah), memorize short surahs, memorize hadith, pray daily ablution and memorize readings and prayer movements. The goal is to guide and direct children towards goodness and truth.